Optimisasi Pengelolaan Karyawan dan Proyek Melalui Sistem Berbasis Web di PT Raja Perkasa - Muhamad, Fachrul Pralienka Bani; Islakhuddin, Fauzan; Ismantohadi, Eka (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
PT Raja Perkasa, a construction company, faces challenges in operational management and employee performance. This study aims to develop a web-based management system to address these issues. The application includes management of portfolios, partner data, collaboration proposals, project data, and employee information, along with attendance tracking. Additional features include leave management, resignation processing, and issuing warnings to employees. The Waterfall method was applied, covering requirement analysis, design, development, testing, deployment, and maintenance. Laravel served as the framework, while MySQL was used as the database management system, enhancing development efficiency and effectiveness. After local testing, the application was hosted for user access. During maintenance, bug fixes were performed, and user satisfaction was measured through questionnaires from 23 respondents, comprising seven user types: admin, project manager, owner, HR, employees, company partners, and application visitors. Results indicate strong agreement among all user types that the application features met their needs and provided a positive experience. However, further development is needed to add employee recruitment, project scheduling, and financial management features, with an emphasis on data security. This application aims to strengthen PT Raja Perkasa's position in the construction industry and improve project management and employee productivity